11Beta-hydroxysteroid dehydrogenase type 1 in human disease: a novel therapeutic target. - Tomlinson, J (2005)
Patients with cortisol excess, Cushing's syndrome, develop a classical phenotype characterized by central obesity, hypertension, and increased cardiovascular mortality. Whilst this observation points to the importance of glucocorticoids, circulating cortisol excess is rare and does not explain the pathogenesis of many common conditions. At a tissue specific level, the enzyme 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1) locally regenerates active cortisol from inactive cortisone amplifying glucocorticoid receptor activation in the context of normal circulating cortisol levels. Increased 11beta-HSD1 activity and expression have been implicated in the pathogenesis of many common conditions including, obesity, insulin resistance, the metabolic syndrome, polycystic ovarian syndrome, osteoporosis and glaucoma. Furthermore, selective 11beta-HSD1 inhibition has been proposed as a novel therapeutic strategy in many of these conditions. Here we review the role of 11beta-HSD1 in human disease and discuss the impact of selective 11beta-HSD1 inhibition.